Three Yeast Proteins Related to the Human Candidate Tumor Suppressor p33(ING1) Are Associated with Histone Acetyltransferase Activities - Loewith, Robbie (American Society for Microbiology, 2000)
Three Saccharomyces cerevisiae proteins (Yng1/YOR064c, Yng2/YHR090c, and Pho23) and two Schizosaccharomyces pombe proteins (Png1/CAA15917 and Png2/CAA21250) share significant sequence identity with the human candidate tumor suppressor p33(ING1) in their C-terminal regions. The homologous regions contain PHD finger domains which have been implicated in chromatin-mediated transcriptional regulation. We show that GFP-Yng2, like human Ing1, is localized in the nucleus. Deletion of YNG2 results in several phenotypes, including an abnormal multibudded morphology, an inability to utilize nonfermentable carbon sources, heat shock sensitivity, slow growth, temperature sensitivity, and sensitivity to caffeine. These phenotypes are suppressed by expression of either human Ing1 or S. pombe Png1, suggesting that the yeast and human proteins are functionally conserved. Yng1- and Pho23-deficient cells also share some of these phenotypes. We demonstrated by yeast two-hybrid and coimmunoprecipitation tests that Yng2 interacts with Tra1, a component of histone acetyltransferase (HAT) complexes. We further demonstrated by coimmunoprecipitation that HA-Yng1, HA-Yng2, HA-Pho23, and HA-Ing1 are associated with HAT activities in yeast. Genetic and biochemical evidence indicate that the Yng2-associated HAT is Esa1, suggesting that Yng2 is a component of the NuA4 HAT complex. These studies suggest that the yeast Ing1-related proteins are involved in chromatin remodeling. They further suggest that these functions may be conserved in mammals and provide a possible mechanism for the human Ing1 candidate tumor suppressor.